In a lonely place - Antheil, George 1900-1959 (<<The>> Criterion Coll., 2016)
"Ein Hollywood-Autor gerät unter Mordverdacht. Sein jährzorniges Verhalten läßt sogar seine Geliebte an ihm zweifeln. Die Liebe der beiden zerbricht, obwohl sich zuletzt seine Unschuld herausstellt. Versiert inszenierter "schwarzer" Hollywoodfilm, der durch Humphrey Bogarts lakonisch-präzises Spiel und raffiniert unterkühlte Dialoge besticht [...]."
Original: USA 1950
Bildformat 1.33:1, new 2K digital restoration, with uncompressed monaural soundtrack
Bonus: new audio commentary featuring film scholar Dana Polan ; "I’m a stranger here myself", a 1975 documentary about director Nicholas Ray, slightly condensed for this release ; new interview with biographer Vincent Curcio about actor Gloria Grahame ; piece from 2002 featuring filmmaker Curtis Hanson ; radio adaptation from 1948 of the original Dorothy B. Hughes novel, broadcast on the program Suspense ; an essay by critic Imogen Sara Smith
Keywords: Film; Blu-Ray-Disc